The risk of developing depression in tuberculosis survivors: a nationwide cohort study in South Korea - Kim, Hyun Soo; Jung, Jin Hyung; Han, Kyungdo; Kim, Hyewon; Jeon, Hong Jin (Frontiers in Psychiatry, 2025)
BackgroundDespite a high tuberculosis incidence in Korea, the association between tuberculosis and depression remains underexplored. This study aims to assess depression risk in tuberculosis survivors.MethodsUtilizing South Korea’s National Health Insurance Sharing Service (NHISS) database, we conducted a gender-age-matched analysis comparing depression risk between tuberculosis survivors and the general population.ResultsThis study included 137,996 participants, of whom 34,499 had tuberculosis history, and 103,497 age- and sex-matched individuals were selected as the control group. The risk of developing depression was higher in tuberculosis survivors than in the control group (aHR 1.20, 95% CI 1.15-1.25). In men, the risk of developing depression was 1.32 times (95% CI 1.25-1.39) compared with 1.05 times (95% CI 0.98-1.12) in women. Those taking para-aminosalicylate, cycloserine, and prothionamide had a higher risk of developing depression compared to those using other anti-tuberculosis drugs, with the risk ratio ranging from 1.27 to 1.61.ConclusionTuberculosis survivors had a higher risk of developing depression compared to the control group. Although the prevalence of depression was higher in women compared to men, the risk of developing depression was higher in male tuberculosis survivors than in the control group, in contrast to the findings in women. The risk of developing depression in tuberculosis survivors differed depending on the anti-tuberculosis drug used and was mainly high in most of the second-line anti-tuberculosis drugs.